Turkish health professional's attitude toward euthanasia - Karadeniz, Guelten; Yanikkerem, Emre; Pirincci, Edibe; Erdem, Ramazan; Esen, Aynur; Kitapcioglu, Guel (Baywood Publ Co Inc, 2008)
The cross-sectional study was administrated between April and September 2006. Participants are doctors, nurses, and midwives. Between these dates we met only 750 health staff (doctor, nurse, and midwife). Six hundred thirty-two of them responded to our questionnaire, 122 of them were in Manisa city, and 5 10 of them in Erciyes. We sought to identify variables that contribute to euthanasia attitude, including demographics, in order to demonstrate Turkish doctors', nurses', and midwives' attitudes toward euthanasia and to compare their attitudes in this regard. The data was collected by a two-part questionnaire. The first part included questions about the health personnel; the second part comprised the euthanasia (Medical Staff's Attitude toward Euthanasia) scale. The scale was developed by the researcher to measure the attitude of healthy staff euthanasia. The SPSS was used to analyze the data. Student t-test, ANOVA, Mann Whitney U, and Kruskal Wallis were used to evaluate the data. The p value 0.05 (95% confidence interval) was accepted as significant. In our study, professional groups are compared with all the factors but there is a significant difference only between social cost and professional groups.
Keywords: Assisted Suicide; Life; Nurses; Experiences; Decisions; Australia; Death; End; Act